2019
DOI: 10.21107/agriekonomika.v8i2.5427
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Preferensi Konsumen Kopi di Lingkungan Akademik Universitas Swadaya Gunung Jati Cirebon Pada Era Revolusi Industri 4.0

Abstract: Preferensi konsumen menunjukkan tingkat kesukaan seseorang terhadap suatu produk dan penentuan kesukaannya berdasarkan atribut-atribut yang ada pada produk tersebut.  Namun demikian, diantara atribut-atribut selalu ada yang paling dipertimbangkan sebagai dasar pengambilan keputusan pembeliannya. Penelitian ini bertujuan untuk mengetahui preferensi konsumen terhadap keseluruhan atribut pada produk minuman kopi saset dan mengetahui atribut mana yang paling dipertimbangkan konsumen dalam memutuskan pembeliannya p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
0
0
0
1
Order By: Relevance
“…The loading factor value of 0.75 can be seen in Figure 2 and Table 3 above. The results of this study are in line with the results of the study Wachdijono et al, (2019); Zulfi et al, (2018) showing that the level of coffee consumer preference lies in the brand and Darmansyah et al, (2020); Fathurrahman et al, (2023); Putra & Ekawati (2017); Ratnasari and Wachdijono (2021), which explain that price affects consumer purchases. However, this is contrary to the results of the research by Anwardin et al (2021), which concluded that price has no significant effect on the sustainability of fish feed stores and also contradicts the law of demand, which says: "if the price increases, the number of products demanded will decrease" (Gilarso, 2008;Sukirno, 2014).…”
Section: The Influence Of Price (X1) On Coffee Shop Business Sustaina...supporting
confidence: 90%
“…The loading factor value of 0.75 can be seen in Figure 2 and Table 3 above. The results of this study are in line with the results of the study Wachdijono et al, (2019); Zulfi et al, (2018) showing that the level of coffee consumer preference lies in the brand and Darmansyah et al, (2020); Fathurrahman et al, (2023); Putra & Ekawati (2017); Ratnasari and Wachdijono (2021), which explain that price affects consumer purchases. However, this is contrary to the results of the research by Anwardin et al (2021), which concluded that price has no significant effect on the sustainability of fish feed stores and also contradicts the law of demand, which says: "if the price increases, the number of products demanded will decrease" (Gilarso, 2008;Sukirno, 2014).…”
Section: The Influence Of Price (X1) On Coffee Shop Business Sustaina...supporting
confidence: 90%
“…Efforts to achieve or increase consumer loyalty can be accomplished by improving the quality of barista friendliness. Additionally, coffee shop entrepreneurs can focus on one or a combination of elements of the marketing mix, such as product diversity, taste, and branding (Wachdijono et al, 2019) The Effect of Customer Satisfaction on Customer Loyalty The study's results indicate that customer satisfaction has a significant and positive impact on loyalty, consistent with previous research (Joshua Cuñado et al, 2020;Mudjiyanti & Sholihah, 2022). Therefore, coffee shop entrepreneurs should improve customer satisfaction by enhancing the quality of their baristas, the comfort of the shop's atmosphere, or other relevant aspects.…”
Section: The Effect Of Barista On Customer Loyaltymentioning
confidence: 99%
“…In addition, based on research results, consumer loyalty can also be caused by factors: innovative products (Wachdijono et al, 2022;Mustamu and Ngatno, 2021;Aryoni et.al., 2019), Affordable price (Maulidio and Dwiastani, 2022;Setiawan et. al., 2021;Ratnasari and Wachdijono, 2021;Anggraini and Silitonga 2019), Product Brand Image (Susianti et al 2021;Ismiyatiningsih 2021;Wachdijono et. al., 2019), and barista service quality (Tsalatsa, 2021;Julianto et.…”
Section: Resultsmentioning
confidence: 99%